Competitive Advantages of Transnational Corporations under the Global Economy Conditions (Economics and region, 2018)
The paper is devoted to the analysis of the competitive advantages of transnational corporations under the conditions of the modern world economy. Taking into account the dynamism of the development of the global economy, the sources of the formation of competitive advantages of the companies operating on the world market are constantly changing. This necessitates further analysis. The process of globalization makes adjustments to many of the economic and social processes that take place in a global society. Under the influence of globalization, competition turns to be global too. The process of gaining and maintaining an international competitive advantage is rather complicated. Firms gain competitive advantages by finding new ways to compete in their industry. The article identifies innovations that give company a competitive edge in the global market. In most cases innovations result from corporate or university R&D and are combined with educational strategies. Transnational corporations have significant advantages over the firms operating only within national markets. International companies are resistant to the effects of volatile macro-environment in a globalized world, which is the main source of their competitive advantages. The authors of the article outline some other important competitive advantages of a transnational corporation in the modern global economy. Among them are the following: concentration of resources (capital, knowledge, personnel, raw materials); flexibility of investment policy; possibility of participation in strategic alliances; corporate social responsibility; standardization of activity, which is combined with a certain level of adaptation to the conditions of the host country, etc. Corporate intellectual capital includes inter-organizational relations, as the source of competitive advantage of contemporary enterprises, which forms networks and value chains. The paper concludes that transnational corporations have much bigger competitive advantages than national companies or even states that are subjects of global competition. New technologies contribute to consolidating the competitive advantages of corporations as they lead to lower production costs and product prices, increase their quality. The development of new products is at the core of the struggle for the market, attracting consumers and trading partners.
Keywords: competitive advantages; transnational corporations; globalization; competition; international competitiveness